Nuclear Data Sheets for A=150 - Basu, S.K.; Sonzogni, A.A. (Nuclear data sheets, 2013)
The experimental results from the various reaction and decay studies leading to nuclides in the A=150 mass chain have been reviewed. These data are summarized and presented, together with the adopted level schemes and properties, for the nuclides from Cs(Z=55) through Lu(Z=71). This evaluation replaces the previous evaluation by E. der Mateosian and J. K. Tuli (1995De28), which appeared in Nuclear Data Sheets 75, 827 (1995).